Attentional capture by social stimuli in young infants - Gluckman, Maxie; Johnson, Scott P. (Frontiers in Psychology, 2013)
We investigated the possibility that a range of social stimuli capture the attention of 6-month-old infants when in competition with other non-face objects. Infants viewed a series of six-item arrays in which one target item was a face, body part, or animal as their eye movements were recorded. Stimulus arrays were also processed for relative salience of each item in terms of color, luminance, and amount of contour. Targets were rarely the most visually salient items in the arrays, yet infants' first looks toward all three target types were above chance, and dwell times for targets exceeded other stimulus types. Girls looked longer at faces than did boys, but there were no sex differences for other stimuli. These results are interpreted in a context of learning to discriminate between different classes of animate stimuli, perhaps in line with affordances for social interaction, and origins of sex differences in social attention.